Evolution, Technique, and Aesthetic Value of Silk Fabric: A Review of Recent Literature - Feby Triadi (Universitas Cahaya Prima, 2024)
Silk fabric has long been a symbol of luxury and a cultural representation of traditional artisan communities. This research adopts an ethnographic approach to explore production practices, weaving techniques, motifs and social meanings of silk fabric in craftsmen communities. Data was collected through participant observation, in-depth interviews, and visual documentation, and analyzed thematically to understand the relationship between production techniques, material quality, and aesthetic value. The research results show that the process of making silk cloth not only integrates local knowledge and cultural symbolism, but also technical innovation that adapts to modern market needs. These findings emphasize the importance of preserving textile heritage through sustainable approaches, while providing an empirical contribution to the textile literature and material culture studies. These findings provide a basis for developing strategies for empowering artisan communities, product innovation, and conservation of local wisdom in the contemporary textile industry.